Geo-spatial technologies for carbon sequestration monitoring and management - Vijayanathan, Jeyanny; Balasundram, Siva Kumar; Mohd Hanif, Ahmad Husni (Science Publications, 2011)
Problem statement: Globally, the quantification of Carbon Sequestration (CS) potential of various ecosystems is a challenge. There is an urgent need for technologies that can quantify CS potential cost-efficiently in a repeated and organized manner. Approach: Remote Sensing (RS) and Geographic Information System (GIS) have great potential in current estimation, future prediction and management of carbon sequestration potential in terrestrial ecosystems. This review discusses the current utilization of RS and GIS technologies in CS management in various sectors. Results: Deployment of RS and GIS for CS sequestration improves accuracy, reduces costs, increases productivity, and provides current observations from a regional scale. Conclusion: This review demonstrates the synergistic role of RS and GIS technologies in improving CS management.